Integrated Marketing Communication Strategy in Promoting Advertisements Explore Yogyakarta Borobudur Temple - Uva, Iva Mas; Eva Ariati; M.Ruslan Amiruddin; Dicka Tegarisnandy; Endah Fantini (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The Holistic Marketing Communication Strategy at PT. Taman Wisata Candi Borobudur Prambanan and Ratu Boko aims to introduce the company as the manager of world heritage sites and also to raise public awareness of the importance of preserving Borobudur, Prambanan, and Ratu Boko temples as educational tourist destinations. This study aims to analyze how the promotional strategy of PT. Taman Wisata Candi Borobudur Prambanan and Ratu Boko promotes these world heritage sites and links them with action theory. The research method used in this study is qualitative descriptive with an approach highlighting the quality, value, and meaning behind the facts. Based on the research results, it is shown that the marketing strategy of PT. Taman Wisata Candi Borobudur has gradually succeeded in improving service quality, facilities, and promotion, and has gained recognition from the community in managing these temples. Although visitor numbers have not increased significantly, these changes are reflected in various national and international awards received by the company. This enhances the company's confidence as part of national pride in the global competition in the tourism industry